Phytochemical, Antibacterial and Antioxidant Activities Test of Three Macro-Algae Phaeophyceae Extracts from Pulau Tidung Coastal Kepulauan Seribu - Sri Handayani; Suprihatin Suprihatin; Retno Widowati; Nyoman Yudi; Indra Rahayu (Journal of Tropical Biodiversity, 2020)
Macro-algae is a Thallophyta plant that has been known to have potential as a food and medicine ingredient, one of that is in the Kepulauan Seribu, particularly on Pulau Tidung coastal. Therefore this study aimed to explore the potential of three types of macro-algae: Hormophysa triquerta, Padina austraslis, and Sargassum binderi (Phaeophyceae) on the Pu;au Tidung coastal by revealing the phytochemical content, antibacterial, and antioxidant activity. The design used in this study was completelyrandomized factorial designs. The phytochemicals tested were flavonoid, alkaloid, tannin, saponin, quinon, steroid, and terpenoid. Antibacterial were tested by diffusion wel method on Muller Hinton agar in a petri dishes with a size of 100 mm and a thickness of 10 mm. The three tested macro-algae were extracted using methanol solvent and divided into four concentrations: 5%, 10%, 15%, and 20%. The test bacteria used were Staphylococcus aureus ATCC 6539 and Escherichia coli ATCC 8739. Observation of the antibacterial test was carried out 24 hours after incubation at 370C. Antioxidant activity at concentrations of 100, 200, 300, 500, 700 ppm was carried out by the DPPH (1,1-diphenil-2-pikrylhidrazyl) method. The results of phytochemical tests showed that flavonoids and steroids were found in the three macro-algae tested, while saponins were only found in S. binderi. The results of the inhibition zone showed that the three macroalgae extract tested did not inhibit E. coli bacteria. The largest inhibition zone was shown at a concentration of 20% against S. aureus bacteria, namely, H. triquerta = 10.09 ± 0.89, P. austraslis = 11, 46 ± 1.09, and S. binderi 8.00 ± 1.29. The regression results of the tested macro -algae antioxidant activity showed that the IC50 values were 13,290 ppm (H. triquerta), 3,800 ppm (P. australis), and 4,053 ppm (S. binderi).